Peluang Dan Tantangan Pengelolaan Keuangan Sosial Islam Indonesia Pada Instrumen Filantropi Untuk Kesejahteraan - Kusuma, Nurul Rahmah; Nurrohman, Nurrohman; Nurwahidah, Dede (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
Philanthropic activities are a form of spirit of generosity with a strong theoretical basis contained in the Koran and its practice for prosperity, in the form of endowments, zakat, infaq and sadaqah with the aim of offering solutions to society in empowering existing potential related to humanity. The aim of this research is to outline the challenges and opportunities of philanthropic instruments in Indonesia in maximizing the potential of philanthropic funds. The research method used is a descriptive qualitative approach sourced from secondary data in the form of literature studies originating from journals and other relevant sources related to philanthropic instruments and management institutions. The results of this research show that the potential for community social funds is very large and is not in line with the reality that occurs due to obstacles or problems that are still found in the process of collecting and distributing philanthropic instruments, but these obstacles can be prevented by taking advantage of opportunities to maximize the potential of philanthropic funds so that each entity should synergize with each other. , improve, and support the achievement of the potential of philanthropic instruments for prosperity